Maternal and Child Health in Underdeveloped Areas and State Borders - Yendris Krisno Syamruth; Hari Basuki Notobroto; H Kuntoro (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Mother and child are two vulnerable groups in the family. The health of families inunderdeveloped and border areas is still slowly progress. The high degree of maternal and child health ineach family in underdeveloped and border areas is a benchmark for a national’s public health.Purpose: The study aims to explore the various factors that correlate with the health of mothers and childrenin families who live in underveloped and state borders by using the perspective of supply and demand.Methods: The research was conducted with observational analitic by survey in underdeveloped areas andstate border in 3 border districts in 9 sub-districts with 18 villages in Nusa Tenggara Province, Indonesia.There were 396 families selected from the population by multistage random sampling.Results: The results showed that pregnancy examinations or Antenatal Care services, delivery by healthpersonnel in health facilities; Immunization factors and family planning participation are indicators ofMaternal and Child Health, and home environmental factors, healthy lifestyle factors, infectious diseasefactors, non-communicable diseases, socio-economic factors, and accessibility factors are some of thefactors related to MCH.Conclussion: This study concluded that environmental health factors, healthy lifestyle and behavior,infectious and non-communicable diseases, socio-economic, and accessibility factors are related to thehealth of mothers and children in families living in underdeveloped areas and state borders and AntenatalCare services, delivery by health personnel in health facilities; Immunization factors and family planningparticipation were reflective indicators of Maternal and Child Health in families who live in underdevelopedareas and state borders.